Unilaterale Spondylolysen bei slawischen und slawisch-awarischen Populationen - Vyhnánek, L; Stloukal, M (Anthropologischer anzeiger, 1984)
The authors consider the spondylolysis a polyetiologic abnormality with an important part of congenital factors in its origin. The frequency of spondylolysis can be considered a feature characterizing a population. This opinion is confirmed by finds in skeletal materials from old Slavonic and Slavonic-Avaric cemeteries. The frequency of spondylolysis in the Slavonic part is significantly lower than in the Slavonic-Avaric part of the materials. The share of unilateral spondylolysis is also different (15 and 7%) when comparing these two population groups, but statistically insignificant. The so-called "combined" type of spondylolysis is, however, significantly higher in the number of unilateral cases of spondylolysis than in the bilateral ones.
Keywords: etnicita; spondylolistéza; Spondylolysis; Czechoslovakia; dospělí; Humans; ženské pohlaví; mužské pohlaví; spondylolýza; Adult; Male; Spondylolisthesis; History, Medieval; bederní obratle; Lumbar Vertebrae; dějiny středověku; Ethnicity; lidé; Československo; Female